SAT0243 Clinical Features of Patients with Early Axial Spondyloarthritis Depending on the Presence of Sacroiliitis and the Visualization Method Used. (9th June 2015) - Gubar, E.; Dubinina, T.; Dyomina, A.; Godzenko, A.; Rumyantseva, O.; Shubin, S.; Smirnov, A.; Glukhova, S.; Erdes, S.
Abstract : Objectives: To analyze clinical features of patients (pts) with early axial spondyloarthritis (axSpA) and the possible interrelation of non-radiographic axSpA (nr-axSPA) and ankylosing spondylitis (AS) Methods: 150 pts with axSpA and <5 years duration of inflammatory back pain (ASAS criteria) were examined following ASAS guidelines. While the axSPA diagnosis was determined by ASAS 2009 criteria, the AC – by mNY 1984 criteria Results: At the first examination, 77 (51.3%) pts had X-ray identified sacroiliitis (xSI) and their AS was determined by the mNY criteria (Group 1). 88 (58.7%) pts had sacroiliitis according to MRI (MRI-SI), while 42 of them also had xSI. 46 (30.7%) pts who had active MRI-SI and had no xSI were graded as pts with nr-aSPA (Group 2). In 27 (18.1%) pts, SI was not determined by any of the visualization methods (they were HLA-B27 positive and additionally they had ≥2 other axSPA symptoms (Group 3). Clinical features of pts from all groups are summarized in the Table. Pts of Groups 1 and 2 were comparable by demographic and clinical characteristics. Psoriasis was more common among pts of Group 2 (13.0%) vs Group 1 (1.3%; p=0.007). In Group 1, there were significantly more males than in Group 3 (49.4% and 18.5%, respectively (p=0.004). Among the SI pts (Groups 1 and 2) acute inflammation phase reactants (ESR and CRP) were significantly higher, than in pts without SI. MRI inflammation of the lumbar spine (LS) was more common among the pts with xSI (Group 1 – 25.7%, Group 3 – 7.4%, p=0.04), as well as low BMD (Z≤-2SD) in the LS (Group 1 – 22.4%., Group 3. – 3.9%, p=0.03). Dactylitis was more common among Group 3 pts as compared to the SI cohort (Groups 1 and 2) (p1-3 =0.05, p2-3 =0.03), as well as enthesitis (p1-3 =0.02, p2-3 =0.04) Conclusions: Patients with nr-aSPA but active MRI-SI should be most probably considered as early AS cases, when they did not yet develop destructive changes in sacroiliac joints. Dactylitis and enthesitis are more common in axSpA patients without signs of SI (both by MRI or X-ray). Disclosure of Interest: None declared